Pathologists are able to differentiate reliably the lamina propria associated with Barrett's musculofibrous anomaly from submucosa in oesophageal endoscopic resections. Issue 6 (19th June 2015) - Kaye, Philip V; O'Donovan, Maria; Mapstone, Nicholas; Disep, Babett; Novelli, Marco; Ragunath, Krish
Abstract : Aims: Endoscopic resection (ER) is the standard therapy for early oesophageal neoplasia and is used for diagnosis and treatment. Accurate staging is especially important, as further treatment depends on this. Because Barrett's mucosa often develops fibromuscular hyperplasia with a fibrotic lamina propria and reduplicated muscularis mucosae, pathologists have expressed concern that it may not be possible to differentiate lamina propria reliably from submucosa in such resections. This study aimed to develop criteria for distinguishing submucosa from abnormal lamina propria and test reproducibility. Methods and results: Virtual slides of oesophagectomy cases with early cancer were reviewed by participants, all gastrointestinal (GI) pathologists. Criteria were agreed for recognition of submucosa – the presence of any of submucosal glands, fat and large muscular vessels. A set of 20 endoscopic resections were then uploaded and 45 areas annotated and participants asked to categorize as submucosa or lamina propria. Agreement was excellent, with 35 areas showing agreement by all pathologists and a further seven areas with four of five agreeing. Paired interobserver kappa values varied between 0.69 and 0.955. Conclusion: With the application of usually easily recognizable criteria, pathologists are able to differentiate submucosa from lamina propria with musculofibrous anomaly in oesophageal ER specimens with a high degree of reproducibility.